2018
DOI: 10.1177/0141076818808427
|View full text |Cite
|
Sign up to set email alerts
|

What should be in hospital doctors' continuing professional development?

Abstract: Objective: To ask those most affected by continuing professional development for senior doctors-patients, other professional groups and doctors themselves-what it needs to encompass. Design: The nominal group technique. Participants: Six groups of between seven and nine members (n ¼ 49). Separate groups were held for nurses and therapists (n ¼ 9), patient representatives (n ¼ 8), medical directors (n ¼ 8), consultants (n ¼ 8) and medical trainees (n ¼ 7). An additional group consisted of 'Darzi Fellows' (n ¼ 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
1
0
7
Order By: Relevance
“…The data revealed that the USM medical graduates are well-recognised by other institutions worldwide through their expertise contribution in health care service, academic and research locally, nationally and internationally. This finding had supported the evidence that a professional doctor does not only focus on the core business as a physician but also actively engaged in other fields at various level (20,21).…”
Section: Discussionsupporting
confidence: 67%
“…The data revealed that the USM medical graduates are well-recognised by other institutions worldwide through their expertise contribution in health care service, academic and research locally, nationally and internationally. This finding had supported the evidence that a professional doctor does not only focus on the core business as a physician but also actively engaged in other fields at various level (20,21).…”
Section: Discussionsupporting
confidence: 67%
“…Em relação a estruturação das ações para o desenvolvimento de recursos humanos verificou-se que baseadas no conceito educação permanente foram descritas exclusivamente no Brasil (Mello et al, 2017;Lavich et al, 2017). As demais realizaram ações denominadas como educação continuada, desenvolvimento profissional contínuo ou não especificaram a estrutura (Besson et al, 2020;Dung et al, 2016;Friesen et al, 2017;Herbers & Heaser, 2016;Jones & Moss, 2019;Martins et al, 2019;Mitchell et al, 2016;Roberts et al, 2017;Wanderlei & Montagna, 2018;Yoon et al, 2016). Apenas um dos artigos descreveu ações realizadas com educação permanente e continuada (Adamy et al, 2018).…”
Section: Estruturas Direcionadas Ao Desenvolvimento Dos Recursos Huma...unclassified
“…As estratégias elencadas pelos hospitais para implementar as ações foram: realização de workshops presenciais e facilitadores clínicos que acompanhavam e auditavam as ações dos educandos (Yoon et al, 2016;Mitchell et al, 2016); simulação realística realizada no local de atuação dos profissionais (Herbers & Heaser, 2016); curso teórico-prático baseado em revisão de literatura prévia e Benchmark em outras instituições (Dung et al, 2016); curso teórico-prático associado à presença de facilitadores denominados como mentores (Friesen et al, 2017); incubadora de aprendizagem (Mello et al, 2017); constituição de um núcleo de educação permanente com facilitadores que fomentam as ações em suas unidades de atuação (Lavich et al, 2017); workshop baseado em atividades on-line e presenciais (Roberts et al, 2017); projeto de extensão universitária com ações para qualificar e desenvolver a formação, capacitação e treinamento em serviço (Adamy et al, 2018); curso on-line em ambiente virtual de aprendizagem (Wanderlei & Montagna, 2018); programa de treinamento proposto após revisão de literatura prévia e levantamento das necessidades de desenvolvimento baseada em competências elencadas pelos profissionais que receberiam as ações (Martins et al, 2019); grupo focal multiprofissional, utilizando a técnica de grupo nominal para definição de ações prioritárias para o desenvolvimento contínuo de um grupo específico de outros profissionais (Jones & Moss, 2019); e adaptação de um programa de treinamento presencial para modalidade on-line durante a pandemia de COVID-19.…”
Section: Estratégias De Implementação Das Açõesunclassified
See 1 more Smart Citation
“…Fiona Moss and Lorelei Jones seized on the true spirit of personal development by asking different groups, from patient representatives to medical directors, what should be prioritised in personal development of senior hospital doctors. 1 Analysis of the group discussion revealed three main themes: developing and supporting the system of care; changes in medical practice; and personal wellbeing and that of colleagues. A patient perspective is an important feature of this study, and a patient voice also emerges in our latest article on empathy.…”
mentioning
confidence: 99%